Regional isoprenoid emission from Eucalyptus grandis forests in northeastern Argentina - Richter, Klaus; Centritto, Mauro; Di Bella, Carlos Marcelo; Posse Beaulieu, Gabriela (2017)
Eucalyptus species are strong source of isoprenoid emission. The objective of the present study was to estimate isoprenoid emissions from Eucalyptus grandis forest crops in the Entre Rios province in the Mesopotamia region of Argentina. The emission rates of isoprene and monoterpenes were measured on individual leaves under; controlled environmental conditions. At 30°C and with a PPFD of 1000 μM m-2 s-1 the emission rate of isoprene emission was 12.5 ± 1.9 nM m-2 s-1 and monoterpenes 15.1 ± 3.1 nM m-2 s-1. Emission was significantly affected by leaf position and decreased significantly from East to West. The most abundant compound emitted was limonene, accounting for between 50 and 68% of the total monoterpene emission. The time course of the isoprene emission course showed its strong dependence on light. On sunny days 42% of the isoprene emission comes from top of the canopy and only 2% from bottom of the canopy. But on overcast days, the relative contribution of diffuse radiation may be larger and can exceed the contribution of direct radiation. A model procedure in a Geographic Information System was implemented to estimate isoprene emissions at a regional scale. A forest inventory, data from a meteorological station and leaf area indices derived from satellite data served as inputs for the model. For the Entre Rios province (78781 km2), the isoprene emission totals up to 39.5 t d-1 on a clear summer day. The methodology applied to estimate isoprenoid emissions on a regional scale contributes to the understanding of carbon exchange between biosphere and atmosphere